Mathematical Study of Impact of Travel Rates of Humans in the Transmission of Dengue Disease - Phaijoo, Ganga Ram; Gurung, Dil B. (Nepal Journal of Science and Technology, 2020)
Dengue is an infectious disease caused by dengue viruses of four serotypes DEN 1 to DEN 4. It is transmitted to humans by the bite of female Aedes mosquitoes. The disease has become a significant public health concern in recent years. Dengue viruses have expanded their geographic range through the movement of infected humans. In the present work, a two-patch epidemic model is proposed to describe the transmission dynamics of dengue disease in patches with the mobility of humans. Different travel rates of humans are considered to study the dynamics of the disease. Different patches are considered to have different disease prevalence. Basic reproduction number of the model is calculated, and some threshold conditions are established to study local stability of the equilibrium points. The travel of humans can help the dengue disease to increase its prevalence and sometimes the travel can be helpful in controlling the spread of the disease. Present work demonstrates that proper control in travel rates is helpful in reducing the spread and dominancy of the disease.